Uji Kinerja Turbin Crossflow Skala Laboratorium Sebagai Pembangkit Listrik - Sudarmanto Jayanegara; Rustam Efendi; Muhammad Hasim; Dary Mochamad Rifqie (Patria Artha Technological Journal, 2023)
The increase in electricity consumption goes hand in hand with the growth of population and industry. Sustainable power plants such as turbines are one option. Turbines and generators are the main components as well as the availability of sufficient water discharge to turn the turbine so that it can be forwarded to the generator. This research was conducted in order to test the performance of a turbine laboratory scale that has been designed. The output power generated in the crossflow turbine is 12.5 Watt to 287.906 Watt for a load of 100 Watt and a variable guide blade with a static head of 0.25 kg/cm